Complexity Leadership Theory: An Interactive Perspective on Leading in Complex Adaptive Systems - and Lichtenstein, Uhl-Bien; Schreiber, Orton; Lichtenstein, Benyamin; Uhl-Bien, Mary; Marion, Russ; Seers, Anson; Orton, James Douglas; Schreiber, Craig (Emergence, 2006)
Traditional, hierarchical views of leadership are less and less useful given the complexities of our modern world. Leadership theory must transition to new perspec-tives that account for the complex adaptive needs of organizations. In this paper, we propose that leadership (as opposed to leaders) can be seen as a complex dynamic process that emerges in the interactive "spaces between" people and ideas. That is, leadership is a dynamic that transcends the capabilities of individuals alone; it is the product of interaction, tension, and exchange rules governing changes in per-ceptions and understanding. We label this a dynamic of adaptive leadership, and we show how this dynamic provides important insights about the nature of leadership and its outcomes in organizational fields. We define a leadership event as a perceived segment of action whose meaning is created by the interactions of actors involved in producing it, and we present a set of innovative methods for capturing and analyzing these contextually driven processes. We provide theoretical and practical implications of these ideas for organizational behavior and organization and management theory.